ANALISIS HUKUM YURISDIKSI INTERNATIONAL CRIMINAL COURT PADA PRE-TRIAL CHAMBER TERHADAP KEDAULATAN NEGARA DALAM IMPLEMENTASI KEBIJAKAN WAR ON DRUGS DI FILIPINA - Atikah Muna; Evi Deliana; Zulfikar Jayakusuma (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2022)
The International Criminal Court is an international criminal tribunalthat has jurisdiction over serious crimes under the Rome Statute. In 2021, theICC Pre-Trial Chamber issued a decision related to the implementation of theWar on Drugs policy in the Philippines. This policy against drugs was bornunder the leadership of President Duterte. However, the implementation of thepolicy was not in accordance with applicable regulations and resulted inthousands of people losing their lives.This type of research is normative legal research using the legalprinciples of universal jurisdiction and complementarity. This research isprocessing data using descriptive methods based on data collected throughliterature studies and literature review.The results of this research, the implementation of ICC jurisdictionbased on universal jurisdiction and the concept of admissibility has a reasonablebasis to be implemented against the Philippines in the case of theimplementation of the War on Drugs. In exercising its jurisdiction, the ICC usesthe principle of complementarity with regard to the Philippines' unwillingnessto carry out the national judicial process.Keywords: ICC-Philippine-War on Drugs-Crimes Against Humanity-Complementarity